Gender Equality In Civic Education Textbook - Nurjanah, Nunung -; Abdulkarim, Aim; Komalasari, Kokom; Bestari, Prayoga (UIN Sunan Kudus, 2023)
Textbooks have an important role to promoting gender equality. Apart from being a source of learning that transmits knowledge, textbooks also form students' values, worldviews and gender roles. This research aims to find out whether the Civic Education textbooks used in the high school in this study have a gender equality perspective. This research uses a qualitative approach with descriptive methods. Collecting data in this research using interview techniques, documentation studies, and literature studies. The data analysis using triangulation. Respondents in this study were Civic Education teachers and class XI students at SMA Negeri 1 Kandanghaur and SMA Negeri 1 Sindang. The results of the study showed that the Civic Education textbooks paid little attention to gender equality which appeared on the cover which did not show equal gender representation; textbook materials and illustrations that have not paid attention to gender equality. Based on the results of this research, it is recommended to integrate gender equality into Civic Education textbooks both in terms of content and illustrations, so that the role of Civic Education as democratic education upholds human rights, including the right to be treated equally without discrimination on any basis, including on the basis of gender can be realized.